A molecular tandem cell for efficient solar water splitting - Wang, Degao (Proc Natl Acad Sci U S A, 2020)
Artificial photosynthesis provides a way to store solar energy in chemical bonds. Achieving water splitting without an applied external potential bias provides the key to artificial photosynthetic devices. We describe here a tandem photoelectrochemical cell design that combines a dye-sensitized photoelectrosynthesis cell (DSPEC) and an organic solar cell (OSC) in a photoanode for water oxidation. When combined with a Pt electrode for H(2) evolution, the electrode becomes part of a combined electrochemical cell for water splitting, 2H(2)O → O(2) + 2H(2), by increasing the voltage of the photoanode sufficiently to drive bias-free reduction of H(+) to H(2). The combined electrode gave a 1.5% solar conversion efficiency for water splitting with no external applied bias, providing a mimic for the tandem cell configuration of PSII in natural photosynthesis. The electrode provided sustained water splitting in the molecular photoelectrode with sustained photocurrent densities of 1.24 mA/cm(2) for 1 h under 1-sun illumination with no applied bias.